Perbandingan Metode Biseksi dan Newton-Raphson dalam Memprediksi Jumlah Penduduk Kota Balikpapan - Apriansyah, Apriansyah; Dynova, Anindya Putrie; Wicaksana, Arya Aji; Alfian, Putri Nurafifah Salwa; Misrianto, Misrianto; Jalanidi, Narendra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research examines the increase in the population in Balikpapan City due to the relocation of the National Capital (IKN) and the low participation of the community in the Family Planning (KB) program. The main objective of the study is to compare the effectiveness of two numerical methods, namely the Bisection method and Newton-Raphson method, in predicting the population numbers. Both methods are applied to determine the convergent value of the developed population growth model. The research results show that the Newton-Raphson method has an advantage in terms of convergence speed, requiring only 5 iterations, compared to the Bisection method which requires 26 iterations. This indicates that Newton-Raphson is more efficient in the calculation process. These findings make an important contribution to the development of a more accurate predictive model to support public policy planning, particularly in anticipating population spikes and increasing basic service needs in the buffer areas of IKN.